N Absorption in Nontidal Rice Fields Treated with Microalgae and Nitrogen Fertilizer Application - Buyana, Nova Tri; Gofar, Nuni; Rohim, A. Madjid (Universitas Muhammadiyah Yogyakarta, 2019)
Nutrient elements that are needed by plants during its growth and development is nitrogen. Nitrogen deficiency can cause plants to become necrosis so that plants are not able to photosynthesize well, thus result in lack of food needed by plants. Microalgae can provide nitrogen for rice crops due to its activity. The aim of this research was to know the effect of microalgae from nontidal swamp land to reduce the use of inorganic N fertilizer in paddy field. The study was conducted from January to April 2017, using factorial completely randomized design with two factors, namely isolate and dosage of nitrogen fertilizer. The first factor is the type of the isolate (I), consisting of cultures from the area of rice cultivation (I1), the culture originating from the area around the rice fields (I2) and the cultures of area without rice cultivation (I3) area. The second factor is the dose of nitrogen fertilizer (N) consisting of 0%, 50% and 100%. The results showed that the treatment of the isolate (I) or dosage of nitrogen fertilizer had a significant effect on the weight of 1000 filled grains and the weight of empty grains in the generative phase of rice plant. The interaction between both treatments had a significant effect on the generative (production) phase. The microalgae culture from area of rice cultivation (I1) can contribute nitrogen requirement of 16.23% - 48.71% with an abundance of 7.48 cells ml-1, with the requirement of rice plant nitrogen fertilizer of 45-135 kg ha-1.